Elemental characterization of the cuticle in the marine intertidal pseudoscorpion, Halobisium occidentale. Issue 2 (9th May 2016) - Gallant, James; Hochberg, Rick; Ada, Earl
Abstract: Arthropods are well known to biomineralize and metallize their exoskeletons with naturally occurring elements that function to stabilize the protein component and add hardness to surfaces that endure wear. In this study, we provide the first description of the trace elements in the cuticle of a marine intertidal pseudoscorpion, Halobisium occidentale, using energy‐dispersive x‐ray spectroscopy. We characterized the trace element composition of six regions on four specimens: the prosoma, opisthosoma, tarsal claws, arolia, chelicerae, and pedipalps. In addition to the elements C, O, and N that make up the α‐chitin component of the cuticle, we found 11 trace elements across the body, but only five of these elements were present at significant levels (≥1% wt): Ni, P, Al, Zn, and Fe. The only trace element on both tagmata is P, while the appendages and their structures contain varying amounts of other elements. The tarsal claws are supplemented with Zn and Ni, while the adhesive arolia contain either Ni or P. The pedipalps are enriched with Al along their proximodistal axis, with P, Zn, and Fe present only around the venom pore. The chelicerae have P, Zn, and Fe present only on the distal regions. This study confirms that pseudoscorpions, like many other arthropods, enrich their cuticle with specific elements at precise locations that are important in predation (cheliceral fingers, pedipalps, venom pore) and locomotion (tarsal claws, arolia). This is also the first study to reveal the presence of Al and Ni in any significant quantities in the arthropod exoskeleton.